Sebelipase Alfa Normalizes ALT and Multiple other Disease-Related Abnormalities in Patients with LAL-D - Vinall, Maria (MD Conference Express, 2014)
Lysosomal acid lipase deficiency (LAL-D) is an autosomal genetic recessive disorder that leads to an inability to break down lipid particles in the lysosome, and it is associated with early-onset cirrhosis and cardiovascular disease. This article discusses the Acid Lipase Replacement Investigating Safety and Efficacy trial [ARISE; NCT01757184] was a randomized, double-blind, placebo-controlled phase 3 study designed to evaluate sebelipase alfa in patients with LAL-D.